The Monster Detector - Potter, Ellen, 1963- (Potter, Ellen, 1963- Big Foot and Little Foot, 2018)
Hugo, a young sasquatch, and his friend Gigi use a Monster Detector to find a Green Whistler, but when Hugo's human friend, Boone, joins in, surprises are in store.